Low-concentrated overland flow generated in laboratory experiments: sedimentary structures and fabric - Paisani, Julio Cesar; Pereira Santos, Marcos Cesar; Vinicius de Sordi, Michael (Revista Brasileira de Geomorfologia, 2023)
The sedimentary arrangement generated by overland flows remains an open question, particularly due to the sediment concentration variations of this flow. We create a laboratory experiment to answer a question: what type of facies and structures can low concentration overland flows (≈ 3 vol%) generate in a steep-planar hillslope context with a gently sloped sand accommodation area? Our experiment revealed that nonconfined low concentrated flows were supercritical and turbulent at steep slope. On the sedimentation plain, flows exhibited progressive deceleration implying three flow stages (arrival-flow, intermediate-flow and waning-water flow). In the first stages, flows remained supercritical and turbulent, and in the last stage, they became subcritical and turbulent. Parting lineation was the predominant surface feature for the three flow stages, followed by tool marks, rills and coarse aggregate accumulation. The recurrence of flows implicated in parting lineation reworking, scour-and-fill, and horizontal airscape structures. The arrival-flow stage developed erosive depression, in which sediments were incorporated into the flow. These flow characteristics and sedimentary structures can occur in the real world and are related to overland flow recurrence.